Freezing tolerance in zoysiagrass - Zhang, Qi (Kansas State University, 2007)
Meyer' zoysiagrass (Zoysia japonica Steud.) has been the predominant cultivar used in the transition zone since its release in 1952, primarily because of its excellent freezing tolerance. Six hundred and nineteen zoysiagrass progeny were evaluated over 3 years, and 31 were identified from which one or more cultivars may be released with a finer texture and/or faster establishment and recovery rate compared to Meyer, but with comparable freezing tolerance. DALZ 0102 (Z. japonica), a selection tested in the 2002 National Turfgrass Evaluation Program (NTEP) Zoysiagrass Study has exhibited a faster establishment and recovery rate than Meyer; however, a lower percentage of living rhizomes and nodes was observed in DALZ 0102 compared to Meyer at temperatures [less than or equal to]-15 C in a controlled freezing chamber experiment. Physiological contributors to freezing tolerance, including lipid and fatty acid composition, and endogenous abscisic acid (ABA) levels, were monitored in 'Cavalier' [Z. matrella (L.) Merrill] (cold sensitive, LT[subscript50] = -9.6 C) and Meyer (cold tolerant, LT[subscript50] = -16.2 C) rhizomes during cold acclimation over two years. The most abundant lipids in Zoysia rhizomes were digalactosyl diacylglycerol (DGDG), monogalactosyl diacylglycerol (MGDG), phosphatidylcholine (PC), phosphatidylethanolamine (PE), and phosphatidic acid (PA). It has been suggested that DGDG and PC adopt bilayer structure; whereas MGDG, PE and PA have higher tendency to form a nonbilayer, hexagonal II (HII) phase, which compromises bilayer structure and cell function. Greater fluctuations in PC, PA, and the ratio of PC to (PE + PA) were observed in Zoysia rhizomes during cold acclimation compared to the galactolipids (DGDG and MGDG). Changes in PC and PA levels and the ratio of PC to (PE + PA) were more gradual in Meyer than in Cavalier in one year of the two-year study. There was no clear relationship between double bond indices (DBI) and LT[subscript50] in Cavalier and Meyer; thus, DBI might not be a good indicator of freezing tolerance. Abscisic acid (ABA) levels were higher in Meyer than in Cavalier on all sampling dates and were significantly correlated with LT[subscript50] (r = -0.65, P = 0.01).
Keywords: Zoysiagrass; Freezing; Agriculture, Agronomy (0285)